Valuation considerations of stock based compensation: a case study of semiconductor firms - Engel, Russell; Lyons, Bridget (Journal of Accounting and Finance, 2025)
Equity research analysts and investors remain divided on the treatment of stock-based compensation (SBC) in firm valuation, particularly in discounted cash flow (DCF) and earnings multiples techniques. Many firms and analysts exclude SBC, viewing it as a non-cash expense, while others argue this leads to overvaluation. SBC usage is especially high in the tech sector. This study examines five large semiconductor firms, analyzing SBC levels, its treatment in adjusted earnings, and its impact on share dilution, valuation multiples, and free cash flow calculations. Findings indicate that SBC treatment significantly affects valuation, particularly within the semiconductor industry.
Keywords: Accounting; Actuarial science; Business; Econometrics; Economics; Engineering; Finance; Financial economics; Stock (firearms); Stock options; Valuation (finance); dept.acc

Liberating trapped cash: A case study of Apple and Microsoft - Engel, Russell; Lyons, Bridget; Pannese, Danny A (The Accounting Educators' Journal, 2017)
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

Is cash still trapped? - Aselta, James; Engel, Russell Paul; Lyons, Bridget; Pannese, Danny (Strategic Finance, 2019)
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found